Development of a pendulum machine for measuring contact lens friction. Issue 3 (2nd May 2021) - Mabuchi, Kiyoshi; Iwashita, Hiroko; Sakai, Rina; Ujihira, Masanobu; Hori, Yuichi
Abstract: The lubrication ability of a contact lens is one of its most essential properties because high friction on an eyelid causes discomfort during blinking. Friction measurements allow assessment of lubrication ability. So far, several apparatuses have been developed to measure contact lens friction. However, thus far, ocular physiological conditions including sliding speed and area have been imperfectly realised. Herein, a pendulum‐type friction tester was developed for the assessment of contact lenses under physiological conditions. A high sliding speed of 90 mm/s was achieved thanks to the short oscillation period of the small pendulum. Physiologically, the sliding surface on a contact lens was realised at the fulcrum of the pendulum. The coefficient of friction for the interaction between a contact lens and plastic hemisphere was directly calculated from the decay in potential energy during the free libration of the pendulum. Friction coefficient of a commercially available contact lens in saline solution, 0.1% and 0.3% HA solutions were 0.036, 0.039 and 0.050, respectively. These results were reliable because they ranged within the low levels reported by previous studies. It was shown that the present pendulum machine represents a major advancement in the realisation of physiologically realistic contact lens friction measurement.